2020
DOI: 10.1111/1751-7915.13638
|View full text |Cite
|
Sign up to set email alerts
|

COVID 19: challenges for virologists in the food industry

Abstract: The COVID-19 pandemic is not only a challenge for public health and hospitals, but affects many aspects of our societies. This Lilliput minireview deals with problems that the pandemic causes for the food industry, addressing the presence and persistence of SARS-CoV-2 in the food environment, methods of virus inactivation and the protection of the food worker and the consumer. So far food has not been implicated in the transmission of the infection, but social disruptions caused by the pandemic could cause pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 91 publications
0
38
0
5
Order By: Relevance
“…This is mainly because the situation is rapidly evolving on COVID-19, particularly on viral contamination of foods and associated risks of SARS-CoV-2 transmission, which have only started attracting public and regulatory concerns after the recent events. Most of the evidence on SARS-CoV-2 detection on frozen foods appeared between July-August 2020, weeks or months later after the recent discussions on food-associated transmission of COVID-19 (Ceylan et al 2020;Eslami and Jalili 2020;Rizou et al 2020;Sharma et al 2020;Zuber and Brüssow 2020). Further, studies on the stability of SARS-CoV-2 in food environments only began to appear in early July 2020 (Fisher et al 2020;Harbourt et al 2020).…”
Section: Environmental Chemistry Lettersmentioning
confidence: 99%
“…This is mainly because the situation is rapidly evolving on COVID-19, particularly on viral contamination of foods and associated risks of SARS-CoV-2 transmission, which have only started attracting public and regulatory concerns after the recent events. Most of the evidence on SARS-CoV-2 detection on frozen foods appeared between July-August 2020, weeks or months later after the recent discussions on food-associated transmission of COVID-19 (Ceylan et al 2020;Eslami and Jalili 2020;Rizou et al 2020;Sharma et al 2020;Zuber and Brüssow 2020). Further, studies on the stability of SARS-CoV-2 in food environments only began to appear in early July 2020 (Fisher et al 2020;Harbourt et al 2020).…”
Section: Environmental Chemistry Lettersmentioning
confidence: 99%
“…Coronaviruses including SARs-CoV-2 are known to be susceptible to and easily inactivated by certain biocidal agents such as chlorine and its derivate and ethanol ( Quevedo-León et al, 2020 ). Zuber and Brüssow (2020) indicated that surface disinfection to inactivate human and animal coronaviruses can be achieved with 62–71% ethanol, 0.5% hydrogen peroxide, or 0.1% sodium hypochlorite within 1 min. Table 2 reports various chemical disinfectants against coronaviruses.…”
Section: Inactivation Of and Control Measures For The Sars-cov-2 Virumentioning
confidence: 99%
“…Businesses like Food Industries are getting impacted to maintain proper supply chain as many of the workers are falling sick to SARS-CoV-2. In order to create safe food environment, this companies are applying antimicrobial coatings to high touch surfaces like doors, handles, touch screen to inactivate the virus [27]. Similarly, Employees working in the retail sectors like shopping malls, Grocery stores who has direct customer exposure are 5 times more likely to have tested positive for SARS-CoV-2 [28].…”
Section: Literature Reviewmentioning
confidence: 99%